Nanofiber composite forward osmosis membranes : synthesis, characteristics and applications - Song, Xiaoxiao (2014)
Energy and water shortages are serious hand-in-hand challenges we are facing in 21st century. As the water demands increase exponentially with the expansion of human territory in all aspects, the current energy source that we heavily rely on, the fossil fuel, is going to be depleted in the next several decades. As a result, the economic efficiency of the seawater and brackish water desalination, the only two sectors that could increase water supply for us, has spearheaded in the water purification related research and technologies. Forward osmosis (FO), a natural process in which water naturally permeate from a low salt concentration feed solution to a high salt concentration draw solution due to osmotic pressure difference, has provided a smart approach to lower the energy cost of reverse osmosis processes. Through this process, both fresh water and renewable energy are able to be produced through salinity gradient, provided that appropriate membrane and system configuration can be developed.